Phylogenetic insights into Andean plant diversification - Luebert, Federico; Weigend, Maximilian (Frontiers in Ecology and Evolution, 2014)
Andean orogeny is considered as one of the most important events for the development of current plant diversity in South America. We compare available phylogenetic studies and divergence time estimates for plant lineages that may have diversified in response to Andean orogeny. The influence of the Andes on plant diversification is separated into four major groups: The Andes as source of new high-elevation habitats, as a vicariant barrier, as a North-South corridor and as generator of new environmental conditions outside the Andes. Biogeographical relationships between the Andes and other regions are also considered. Divergence time estimates indicate that high-elevation lineages originated and diversified during or after the major phases of Andean uplift (Mid-Miocene to Pliocene), although there are some exceptions. As expected, Andean mid-elevation lineages tend to be older than high-elevation groups. Most clades with disjunct distribution on both sides of the Andes diverged during Andean uplift. Inner-Andean clades also tend to have divergence time during or after Andean uplift. This is interpreted as evidence of vicariance. Dispersal along the Andes has been shown to occur in either direction, mostly dated after the Andean uplift. Divergence time estimates of plant groups outside the Andes encompass a wider range of ages, indicating that the Andes may not be necessarily the cause of these diversifications. The Andes are biogeographically related to all neighbouring areas, especially Central America, with floristic interchanges in both directions since Early Miocene times. Direct biogeographical relationships between the Andes and other disjunct regions have also been shown in phylogenetic studies, especially with the eastern Brazilian highlands and North America. The history of the Andean flora is complex and plant diversification has been driven by a variety of processes, including environmental change, adaptation, and biotic interactions